The effect of job stability is one of the dimensions of incentives in improving the performance of workers in the agricultural sector (Field study in the Agriculture Directorate in Latakia) - بدور, هديل (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The study aimed to determine the effect of job stability in its dimensions (group cohesion, feeling of security, participation in decision-making, planning and development of the human resource) in improving the performance of workers in the agricultural sector. The researcher relied on the descriptive approach to describe the research variables and analyze them based on the primary data collected. The researcher conducted a field study on the Directorate of Agriculture in Latakia Governorate to collect the necessary primary data. She also measured the variables on all the primary data that was collected through a questionnaire that was designed from While the researcher reviewed previous studies and literature, and in order to test the hypotheses, the researcher transcribed the raw data into a database that was analyzed using SPSS version 20, and the researcher used a set of statistical methods. The study found that there is an acceptable moral effect of job stability in improving the performance of workers in the agricultural sector, as the value of the correlation coefficient reached 0.921, and sig = 0.000, and this is confirmed by the four sub-hypotheses, as the results of the first hypothesis demonstrated the presence of a strong moral effect of group cohesion in improving the performance of workers in The agricultural sector in the Lattakia Agriculture Directorate. The value of sig = 0.000 and the correlation coefficient was 0.832, which is a strong coefficient, which indicates the strong effect of group cohesion in improving the performance of workers. The results of the second hypothesis proved the presence of a strong moral effect of the feeling of security in improving the performance of workers in the agricultural sector in Lattakia Agriculture Directorate, the value of sig = 0.000 and the correlation coefficient was 0.889, which is a strong coefficient, which indicates the strong effect of the feeling of security in improving the performance of workers